Investigating the effect of nanolime treatment on the drying kinetics of Clipsham limestone - Browne, D; Peverall, R; Ritchie, G; Viles, H (Springer Nature, 2023)
Climate change poses an ever-increasing risk to our stone built heritage. Among conservation actions, the use of consolidant products is considered a possible response to this challenge, and the adoption of nanolimes has been widely studied showing promising results. However, while the effectiveness and method of application has been assessed, few studies have probed the changes in drying kinetics following treatment. In fact, a drastic alteration of the water transport might lead to further anomalies. This study investigates the influence of nanolimes dispersed in ethanol on the drying kinetics of Clipsham limestone using cavity ring-down spectroscopy. The degree of treatment was assessed by gravimetry, Raman spectroscopy, optical microscopy, colorimetry, optical profilometry and thin section analysis. Results showed an increase in the dry mass, observable colour changes and decrease in surface roughness. Small but reproducible increases were observed in the evaporation flux for phase I behaviour following treatment, however, no changes were observed in the total mass of water released or the phase II diffusivity. Determination of the activation energy associated with phase II drying was unchanged following treatment . These results indicate that following treatment there has been little-to-no change in the internal surfaces and structure of the stone to affect vapour transport.